Realtor services in the Republic of Kazakhstan - Zhaskayrat, M.; Nurzhanova, A.S. (KSU Publ., 2017)
The article deals with certain issues related to the specifics of regulating realtor activity. The authors of the article paid attention to the study of various aspects of the legal relations arising from the contract of purchase and sale, exchange, hiring of premises. The article deals with topical problems of realtor services’ improving. In the legal literature there is no universally recognized legal norm regulating realtor activity in the Republic of Kazakhstan. This activity is regulated solely by the norms of the Civil Code of the Republic of Kazakhstan on provision of paid services. The essence of realtor activity as a specific business process, which is an indispensable element of the market infrastructure ensuring the efficient functioning of the real estate market, is disclosed. The authors made a legal analysis of the civil legislation of Kazakhstan regulating realtor activity and on this basis proposals aimed at improving legislation were made.
Қазақстан Республикасындағы риэлтерлік қызмет көрсету
Риэлторские услуги в Республике Казахстан
Keywords: civil law; service; realtor activity; rent; residential and commercial real estate; property rights; sales contract